Evaluation of buffer management control on providing guaranteed service - Koh, Nyet Kheng. (2008)
The main objective of this project is to evaluate an approach that uses buffer management control with simple FIFO scheduling mechanism to provide rate guaranteed service. The approach uses leaky bucket mechanism and buffer management control on a FIFO queue to provide rate guarantees for various traffics. In addition to that, we propose to integrate an early packet discard mechanism into the buffer management control scheme for an ATM network to improve the efficiency of the system.